Aspirations of becoming a mathematics or a science teacher: A CB-SEM analysis of preservice teachers' self-ascribed identities - Christeodoflor Ramos; Mary Grace Villaflor; Masza Lyn Milano; Danica Kaye Hallarte; Gesselle Batucan; Roselyn Gonzales; Gamaliel Gonzales (Social Sciences and Humanities Open)
Addressing the global shortage of qualified math and science teachers is a serious challenge, especially for developing countries that are losing skilled educators to jobs overseas. The paper examines the factors influencing career aspirations among preservice teachers in mathematics and science, an area that has received limited focused investigation. Using covariance-based structural equation modeling (CB-SEM), the proposed model examines how motivation, social influence, professional identity, and decisional self-efficacy contribute to career decidedness, subsequently informing career aspirations. Data were collected from 615 mathematics and science preservice teachers enrolled in teacher education institutions across the Visayas regions of the Philippines. The CB-SEM results revealed three key findings: (a) motivation significantly predicts teaching career aspirations, (b) career decidedness has a strong direct positive effect on the intention to pursue teaching, and (c) preservice science teachers demonstrate stronger links between motivation, decisional self-efficacy, and career decidedness compared to their mathematics counterparts. These findings have implications for teacher education policy and programs aimed at strengthening aspirations, recruitment, and retention in mathematics and science teaching professions.